Vitamin D status in children with intestinal failure who have achieved enteral autonomy. (23rd June 2021) - Lepus, Chelsea A.; Samela, Kate; Emerick, Karan M.; Mokha, Jasmeet S.
Abstract: Background: Vitamin D deficiency is highly prevalent in children with intestinal failure (IF) who receive parenteral nutrition (PN), but data on vitamin D status after achieving enteral autonomy (EA) are limited. We aimed to evaluate the prevalence of vitamin D deficiency in this population while exploring clinical variables that may be associated with its development. Methods: A retrospective review was performed on 29 children with IF who had achieved EA. Deficiency was defined as a mean serum 25‐hydroxyvitamin D <30 ng/ml. Data Results: Sixty‐six percent of children had at least one deficient level during the study period, with 38% being deficient based on the mean vitamin D levels. Eighty‐four percent had radiologic evidence of osteopenia. Compared with the sufficient group (n=18), the deficient group (n=11) received higher daily mean vitamin D doses (2246 vs 920 IU; P =.02), had shorter remnant small‐bowel length (53.8 vs 82.1 cm; P =.03), and were PN dependent for a longer duration (1.3 vs 0.58 years; P =.01). Univariate analyses revealed longer remnant gut length (odds ratio [OR] = 1.03; P =.04) and shorter duration of PN (OR = 0.26; P =.04) to be significantly associated with sufficient vitamin D status. Conclusion: Vitamin D deficiency and osteopenia are highly prevalent in pediatric patients with a history of IF who have achieved EA, despite enteral supplementation with higher than standard doses. Shorter remnant small‐bowel length and longer duration of PN were associated with vitamin D deficiency. These findings emphasize the importance of prolonged surveillance and highlight the need for alternate dosing regimens.